2022
DOI: 10.1039/d2cc01679f
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of brevijanazines from Aspergillus brevijanus reveals the molecular basis for p-nitrobenzoic acid in fungi

Abstract: The brevijanazines are novel p-nitrobenzoylated piperazines isolated from Aspergillus brevijanus. Their structures were elucidated by spectroscopic analysis, X-ray crystallography and total synthesis. Heterologous biosynthesis, precursor feeding and in vitro microsomal...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 29 publications
3
14
0
Order By: Relevance
“…Fuligopyrone ( 1 ) and fuligopyrone B ( 2 ) were tested for biological activity against the bacteria Bacillus subtilis (ATCC 6633) and Staphylococcus aureus (ATCC 25923), the fungi Candida albicans (ATCC 10231) and Saccharomyces cerevisiae (ATCC 9763), the protozoan Tritrichomonas fetus (KV-1), the mammalian cell lines NS-1 murine myeloma and neonatal foreskin fibroblasts (NFF), and seeds of the plant Eragrostis tef ( Teff ), using previously described methods. , …”
Section: Methodsmentioning
confidence: 99%
“…Fuligopyrone ( 1 ) and fuligopyrone B ( 2 ) were tested for biological activity against the bacteria Bacillus subtilis (ATCC 6633) and Staphylococcus aureus (ATCC 25923), the fungi Candida albicans (ATCC 10231) and Saccharomyces cerevisiae (ATCC 9763), the protozoan Tritrichomonas fetus (KV-1), the mammalian cell lines NS-1 murine myeloma and neonatal foreskin fibroblasts (NFF), and seeds of the plant Eragrostis tef ( Teff ), using previously described methods. , …”
Section: Methodsmentioning
confidence: 99%
“…5. 48 Thus, the absolute conguration of the piperazine core of 94 should also be revised to be 2S,2 ′ S. 49 Structurally, 97 is symmetric, containing two rarely observed N-p-nitrobenzoyl moieties, while its putative biosynthetic precursor 98 contains only one N-p-nitrobenzoyl group. The structures and absolute congurations of 97 and 98 were determined by a combination of spectroscopic analysis and comparison of the spectroscopic data for natural and synthetic 97 and 98.…”
Section: Reviewmentioning
confidence: 99%
“…36 The gene cluster encoding the biosynthesis of p-nitrobenzoyl-containing piperazines 97 and 98 was recently revealed in A. brevijanus. 49 The biosynthetic gene cluster for scherazines 84-91 was characterised from N. scheri. 44 All these characterised gene clusters encode a paired singlemodule NRPS and NmrA-like reductase, as well as other tailoring enzymes, such as cytochrome P450, methyltransferase, 2OG/Fe(II)-dependent dioxygenase, etc., to biosynthesise structurally diverse piperazines (Fig.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of brevijanazine A 29 , a novel p -nitrobenzoic acid derived piperazine from Aspergillus brevijanus , has been confirmed by X-ray crystallography and total synthesis. 24 Heterologous expression and feeding studies identified a cytochrome P450 oxygenase, BvjF, that produces p -nitrobenzoic acid from p -aminobenzoic acid en route to brevijanazine A.…”
mentioning
confidence: 99%